Home Range and Multiscale Habitat Selection of Threatened Thin-Spined Porcupine in the Brazilian Atlantic Forest - Giné, Gastón Andrés Fernandez; De Barros, Eduardo Hoffmam; Duarte, José Maurício Barbanti [UNESP]; Faria, Deborah (Oxford University Press (OUP), 2015)
The threatened and poorly known thin-spined porcupine (Chaetomys subspinosus) is endemic to the highly deforested central portion of the Atlantic Forest of eastern Brazil. In southern Bahia, anecdotal observations suggested that native forest and shade cacao (Theobroma cacao) plantations are important habitats for this species. However, no studies have examined habitat preferences. We estimated the home-range size and determined the factors influencing habitat selection at landscape, home range, and tree scales in the cacao-growing region of southern Bahia. Radiotelemetry data from 21 individuals followed for 3-25 months from April 2005 to November 2013 showed a relatively small home range (0.5-9.5 ha using minimum convex polygon methods), with males showing larger home ranges than females. Habitat selection was congruent across spatial scales, with preference for structurally complex environments at all scales. The tagged porcupines preferred trees that were large, harboring many lianas, and closer to forest limits. Tree selection was specific for each animal activity. On landscape and home-range scales, they preferred secondary forest and avoided structurally simplified, highly disturbed vegetation types such as shade cacao and rubber plantations, early secondary forest, and open areas. All these man-modified habitats were rarely used, if at all, which considerably reduces the suitable habitat within the core distribution area and profoundly impacts conservation.
Keywords: arboreal folivore; Chaetomys subspinosus; porcupine; shade cacao plantation; spatial ecology